2003
DOI: 10.1073/pnas.1537759100
|View full text |Cite
|
Sign up to set email alerts
|

The LIM-homeobox gene Lhx8 is required for the development of many cholinergic neurons in the mouse forebrain

Abstract: Forebrain cholinergic neurons play important roles as striatal local circuit neurons and basal telencephalic projection neurons. The genetic mechanisms that control development of these neurons suggest that most of them are derived from the basal telencephalon where Lhx8, a LIM-homeobox gene, is expressed. Here we report that mice with a null mutation of Lhx8 are deficient in the development of forebrain cholinergic neurons. Lhx8 mutants lack the nucleus basalis, a major source of the cholinergic input to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
230
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(248 citation statements)
references
References 43 publications
16
230
0
2
Order By: Relevance
“…S1D) and CSIs were dramatically reduced in the striatum (Fig. S1 E-G) (8,(12)(13)(14). Interestingly, reduction of CSIs was associated with increased number of Lhx6-expressing striatal interneurons (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…S1D) and CSIs were dramatically reduced in the striatum (Fig. S1 E-G) (8,(12)(13)(14). Interestingly, reduction of CSIs was associated with increased number of Lhx6-expressing striatal interneurons (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Interestingly, reduction of CSIs was associated with increased number of Lhx6-expressing striatal interneurons (Fig. S1F), a characteristic feature of Lhx7-null mice (8,(12)(13)(14). Therefore, upon Cre-mediated recombination, Lhx7 fl is converted into a null allele.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, the basics of a cholinergic transcription factor code are emerging. A variety of experimental approaches has demonstrated that expression of several transcription factors is important (Mash 1, Olig2, Lmx7, Lmx8) or essential (Nkx2.1) for generating forebrain cholinergic neurons (Bachy and Retaux, 2006;Furusho et al, 2006;Marin et al, 2000;Mori et al, 2004;Zhao et al, 2003). Thus, the combined expression of these factors, and their target genes, probably accounts for much of the intrinsic identity of the cholinergic phenotype.…”
Section: A Development Of Cholinergic Systemsmentioning
confidence: 99%